Human umbilical cord mesenchymal stem cells protect MC3T3-E1 osteoblasts from dexamethasone-induced apoptosis via induction of the Nrf2-ARE signaling pathway - Chen Qiu; Zhaowen Li; Puji Peng (Regenerative Therapy, 2024)
Objective: To investigate the protective effect human umbilical cord mesenchymal stem cells (hUC-MSCs) have on Dexamethasone (Dex)-induced apoptosis in osteogenesis via the Nrf2-ARE signaling pathway. Methods: Glucocorticoid-induced osteonecrosis of the femoral head (GC-ONFH) was developed in rats through the administration of lipopolysaccharide and methylprednisolone. The incidence of femoral head necrosis, cavity notch, apoptosis of osteoblasts, and bone density were observed by HE staining, TUNEL staining, and Micro-CT. HUC-MSCs were co-cultured with mouse pre-osteoblast MC3T3-E1. The survival rate of osteoblasts was determined by CCK8, and apoptosis and ROS levels of osteoblasts were determined by flow cytometer. The viability of antioxidant enzymes SOD, GSH-Px, and CAT was analyzed by biochemistry. Nrf2 expression levels and those of its downstream proteins and apoptosis-related proteins were analyzed by Western blotting. Results: In rats, hUC-MSCs can reduce the rates of empty bone lacuna and osteoblast apoptosis that are induced by glucocorticoids (GCs), while reducing the incidence of GC-ONFH. hUC-MSCs can significantly improve the survival rate and antioxidant SOD, GSH-Px, and CAT activity of MC3T3-E1 cells caused by Dex, and inhibit apoptosis and oxidative stress levels. In addition, hUC-MSCs can up-regulate the expression of osteoblast antioxidant protein Nrf2 and its downstream protein HO-1, NQO-1, GCLC, GCLM, and apoptosis-related protein bcl-2, while also down-regulating the expression of apoptosis-related protein bax, cleaved caspase-3, cleaved caspase-9, and cytochrome C in MC3T3-E1 cells. hUC-MSCs improve the ability of MC3T3-E1 cells to mineralize to osteogenesis. However, the promoting effects of hUC-MSCs were abolished following the blocking of the Nrf2-ARE signaling pathway for osteoblasts. Conclusion: The results reveal that hUC-MSCs can reduce Dex-induced apoptosis in osteoblasts via the Nrf2-ARE signaling pathway.